Indian Hadith Scholar Siddiq Hasan Khan’s d.1307/1890 Opinions 19TH Regarding Allah's Attributes - Uzundağ, Sait (Fırat University, 2014)
Khabari attributes such as vach face , yâd hand and istawâ ? sette down are proved in the Qur'ân and Sunnah. Different opinions emerged regarding to that how these attributes should be designated. Overall, Cahmiyya, Mu'tazila and Qadariyya delivered opinion about attributes based on sanctify and negotiation tanzîh . The view of the Ahl-i Hadith about these attributes is to acknowledge that as reported in the Qur'ân and hadith and not to interprete ta’wîl them. Siddiq Hasan Khan, is regarded as one of the most prominent representatives of the school of Ahl-î Hadîth in India in the end of the I9th century. Siddiq Hasan Khan who knows Arabic, Persian and Urdu languages, has been written many works in the field of mysticism, language, literature, history, biography, especially in Tafsîr, Hadîth, Fiqh, Aqâid. One of his studies in his hadith is Avnu al-Bari bi-halli Adillet al-Bukhari which is a commentary written about Zabîdî's d. 893/1488 al-Tacrîd al-Sarih Ahâdis al-Camîi al-Sahih. In this study, we will examine Siddiq Hasan Khan’s approach to some attributes of God from the point of view of aforesaid work

Haberi sıfatlar, Kur’an ve Sünnet'le isbat edilen vech, yed, istiva gibi sıfatlardır. Bu sıfatların nasıl anlamlandırılmaları gerektiği yönündeki farklı görüşler ortay çıkmıştır. Genel olarak Cehmiyye, Kaderiye ve Mu’tezile Allah’ın sıfatları hakkında tenzih ve takdis esasları yönünde görüş bildirmişlerdir. Ehl-i Hadis’in izlediği yol ise bu sıfatlara hakkında Kur’an ve hadiste bildirildiği şekliyle bağlı kalmak ve hiçbir tevil ve teşbihte bulunmamaktır. İşte bu bağlamda Sıddîk Hasan Han da Allah’ın haberi sıfatları hakkında fikirler ileri sürmüştür. Sıddîk Hasan ö. 1307/1890 XIX. yüzyılın sonlarında Hindistan’da Ehl-i Hadis ekolünün en önde gelen temsilcilerinden biri olarak kabul edilmektedir. Arapça, Farsça ve Urduca dillerini bilen ve bu dillerde tefsir, hadis, fıkıh, akaid başta olmak üzere tasavvuf, dil, edebiyat, tarih, biyografi alanlarında da birçok eser kaleme alan velûd bir müelliftir. Onun hadis alanında yaptığı çalışmalardan biri de Zebîdî’nin ö. 893/1488 EtTecrîdu’s-Sarîh li Ehâdisi’l Camîi’s-Sahîh adlı eseri üzerine yazdığı “Avnü’l-Bârî bi-Halli Edilleti’lBuhârî” adlı şerhidir. Biz de bu makalemizde müellifin adı geçen eseri bağlamında onun Allah’ın haberî sıfatlarına yaklaşımını irdeleyeceğiz
XIX. ASIR HİNDİSTAN HADİS ALİMİ SIDDÎK HASAN HAN’IN Ö.1307/1890 ALLAH’IN HABERÎ SIFATLARI İLE İLGİLİ GÖRÜŞLERİ